2011
DOI: 10.1038/ijo.2011.218
|View full text |Cite
|
Sign up to set email alerts
|

Study of eight GWAS-identified common variants for association with obesity-related indices in Chinese children at puberty

Abstract: OBJECTIVE: Genome-wide association studies (GWAS) have identified some common variants associated with obesity risk in European descents. However, their influences on obesity-related indices for the Chinese children at puberty are not widely clear yet. To address this question, we conducted a study that aims to examine effects of eight previously reported GWAS singlenucleotide polymorphisms (SNPs) on four obesity-related indices in a sample of Chinese children aged 10 --12 years. METHODS: Anthropometric indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 50 publications
3
50
3
4
Order By: Relevance
“…One-third of the cohort (n = 173, 33.4 %) was classified as prepubertal, and two-thirds (n = 345, 66.6 %) as pubertal. The median BE scale was 16 [11][12][13][14][15][16][17][18][19][20][21][22], whereas 45.5 % of the cohort was classified with BE. The median insulin level was 20.9 lU/mL (14.7-31.8), and median HOMA-IR was 4.1 (2.8-6.5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One-third of the cohort (n = 173, 33.4 %) was classified as prepubertal, and two-thirds (n = 345, 66.6 %) as pubertal. The median BE scale was 16 [11][12][13][14][15][16][17][18][19][20][21][22], whereas 45.5 % of the cohort was classified with BE. The median insulin level was 20.9 lU/mL (14.7-31.8), and median HOMA-IR was 4.1 (2.8-6.5).…”
Section: Resultsmentioning
confidence: 99%
“…The Portuguese version of the BE scale [13], the result of a procedure of translation and adaptation, as suggested by Herdman's proposal for cross-cultural adaptation of instruments, showed a sensitivity of 97.8 %, a specificity of 47.7 %, a positive predictive value of 66.7 % and a negative predictive value of 95.3 %. In this study, the participants were categorized into groups of absent BE (BE score B17) and present BE (BE score [17). The assessment of dietary intake of the participants was made using the 24-h dietary recall (24hR) dietary survey, with the objective of evaluating the mean absolute energy intake (kcal), percentage of macronutrients (carbohydrates, protein, total fat), and types of dietary fat (saturated, monounsaturated, and polyunsaturated fats).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous studies are focused on populations of European Ancestry and adults. Subsequent studies have attempted to identify the associations in Chinese population, however, the results of GNPDA2, KCTD15, NEGR1, MC4R, SEC16B and ETV5 are inconsistent (Cheung et al, 2010;Wang et al, 2012;Hong et al, 2013;Xi et al, 2013). In addition, ten other obesity-related genes (LYPLAL1, MSRA, TFAP2B, MAP2K5, RPL27A, PAX5, CDKAL1, AMD1, HOXB5 and OLFM4) have not been examined in Chinese children.…”
Section: Introductionmentioning
confidence: 87%
“…Xi et al [22] confirmed the synthetic effect of SNPs on the indices of adiposity and risk of obesity in Chinese girls but not in Chinese boys. Another study performed in Chinese children also indicated that gender differences may exist in various obesity-related genes [23] . In our study, the reasons for the difference between the sexes may be as follows: 1) the adipose tissue distribution between women and men is quite different and 2) bone geometric structures vary between genders.…”
Section: Discussionmentioning
confidence: 99%